The order of succession by law. (Journal of actual problems of jurisprudence, 2016)
This article focuses on the order of inheritance by law. Under intestate succession will of the testator in the distribution of the inheritance among the heirs is not involved. Since it is in strict accordance withthe rules established by the State. The article discusses who can be a child of the law, and in what order the heirs are encouraged to inherit. Having considered the successors to the current legislation.
Keywords: inheritance; the heirs; hereditary share; hereditary mass